Menghitung Status Gizi Pada Balita Berbasis Web - Tricahyo, Novendhi; , Dr. Supriyono Heru, M.Sc (2017)
Nutrients are substances that affect the development of the human body so that the function of the body running properly. On toddler nutrition course is very beneficial to the development of the sensory and motor skills. Nutritional status is a situation where the nutritional intake in balance with the needs of the body. If a person or a toddler nutrition intake then the excess is also not good for the body. Certainly every parent want to always know the development of the fruit of their hearts at any time. Therefore needed an application to calculate the nutritional status in children so that parents can monitor directly the nutritional fruit of their hearts. Look at the problems the author will try to create an application that aims so that makes it easy for parents and anyone in General to know their toddler nutrition status in real time. To use the application or user parents must register in advance to the system as user. Then enter your weight, age, and the length of the body of the toddler. The system will process the data would then be known whether toddler nutritional status poor nutrition, lack of, well, or more. This application is made with PHP and MySQL Database is web-based, so easy access wherever the origin have internet network. The results of this research is an application to calculate the nutritional status on the toddler's web-based. This application has also gone through the testing phase with the black-box method and methods questionnaire results was satisfactory although there is still a shortage. Keywords : MySQL, Nutrion, Nutritional Status, PHP